PERAN SISTEM INFORMASI MENEJEMEN DALAM MENINGKATKAN EFEKTIVITAS TATA KELOLA LEMBAGA PENDIDIKAN ISLAM - Yanuarti Pertiwi, Fauza; Annur, Saipul; Rosad, Ade (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid digital transformation demands that Islamic educational institutions promptly adopt Management Information Systems (MIS) as a strategic instrument in institutional governance. This study aims to analyze the role of MIS in enhancing the effectiveness of Islamic educational institution governance, identify factors influencing successful implementation, and formulate a strategic model for MIS application grounded in Islamic governance values. A qualitative method with a library research approach was employed, involving systematic review of relevant scientific literature. The findings reveal that MIS contributes significantly to integrating the management of student data, curriculum, finance, and human resources within a unified digital ecosystem. MIS has also proven effective in improving reporting transparency, strengthening institutional accountability, and supporting data-driven decision making by institutional leaders. The success of MIS implementation is strongly influenced by technological infrastructure readiness, digital literacy levels among human resources, leadership commitment, and system sustainability. The novelty of this research lies in the integration of an Islamic governance approach within the MIS implementation framework, positioning the values of amanah, honesty, and musyawarah as the ethical foundation of system operations. This study concludes that strategically and contextually implemented MIS will serve as the primary pillar in realizing modern, efficient, accountable, and dignified governance of Islamic educational institutions